2021
DOI: 10.3390/molecules26020302
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Polyphenol Enriched Complex Plants Extract on Metabolic Dysfunctions Associated with Obesity and Related Nonalcoholic Fatty Liver Diseases in High Fat Diet-Induced C57BL/6 Mice

Abstract: Background: Currently, obesity is a global health challenge due to its increasing prevalence and associated health risk. It is associated with various metabolic diseases, including diabetes, hypertension, cardiovascular disease, stroke, certain forms of cancer, and non-alcoholic liver diseases (NAFLD). Objective: The aim of this study to evaluate the effects of polyphenol enriched herbal complex (Rubus crataegifolius/ellagic acid, Crataegus pinnatifida Bunge/vitexin, chlorogenic acid, Cinnamomum cassiaa/cinnam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Hence, this result establishes a factual basis for further research. To date, it has been well documented that a majority of natural plant compounds (including CGA) show a spectacular antioxidant capacity (Liang and Kitts, 2015;Hussain et al, 2021). Of note, the basic and most widely used biological property of CGA is antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this result establishes a factual basis for further research. To date, it has been well documented that a majority of natural plant compounds (including CGA) show a spectacular antioxidant capacity (Liang and Kitts, 2015;Hussain et al, 2021). Of note, the basic and most widely used biological property of CGA is antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease deposition of fat droplets in the liver, and intima media thickness in the aorta. It also increased the activity of carnitine palmityl transferase (CPT) and significantly decreased the activity of β-hydroxylβ-methylglutamyl-coA reductase and fatty acid synthase (FAS) ( 48 ), effectively protecting metabolic dysfunction. Studies have revealed that the combined action of CGA and caffeine can help prevent obesity, as well as metabolic and lifestyle-related diseases through the AMPKα-LXRα/SrebP-1C pathway.…”
Section: The Biological Activity and Mechanism Of Chlorogenic Acidmentioning
confidence: 99%
“…Vitexin is a natural flavonoid compound with multiple pharmacological activities such as lipid metabolism modulation, anti-inflammation. Vitexin can not only suppress de novo lipogenesis but also enhance fatty acid oxidation and lipolysis, in addition, it can improve insulin signaling in HFD mice possibly through binding to leptin receptor and activating AMPK [ 33 , 34 ]. Furthermore, vitexin could ameliorate chronic stress combined with NAFLD mice induced by HFD, through inhibiting TLR4/NF-κB signaling and the expression of proteins related to fatty acid synthesis [ 35 ].…”
Section: Effects and Mechanisms Of Commonly Used Single Herb Drugs In Tcm On Nafldmentioning
confidence: 99%